Bank Financing for SMEs around the World : Drivers, Obstacles, Business Models, and Lending Practices - Beck, Thorsten; Demirgüç-Kunt, Asli; Martínez Pería, María Soledad (Washington, DC: World Bank, 2012)
Using data from a survey of 91 banks in 45 countries, the authors characterize bank financing to small and medium enterprises (SMEs) around the world. They find that banks perceive the SME segment to be highly profitable, but perceive macroeconomic instability in developing countries and competition in developed countries as the main obstacles. To serve SMEs banks have set up dedicated departments and decentralized the sale of products to the branches. However, loan approval, risk management, and loan recovery functions remain centralized. Compared with large firms, banks are less exposed to small enterprises, charge them higher interest rates and fees, and experience more non-performing loans from lending to them. Although there are some differences in SMEs financing across government, private, and foreign-owned banks - with the latter being more likely to engage in arms-length lending - the most significant differences are found between banks in developed and developing countries. Banks in developing countries tend to be less exposed to SMEs, provide a lower share of investment loans, and charge higher fees and interest rates. Overall, the evidence suggests that the lending environment is more important than firm size or bank ownership type in shaping bank financing to SMEs.